Praktik Dualitas Struktur-Agensi Program Inklusi Keuangan: Studi Refleksi Organization for Women in Self Employment (WISE) Addis Ababa, Ethiopia - Rahmawati, Arifah (Humanities Studies, Post-Graduate Program, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2024)
How do we understand operationalization of structure-agency duality? This paper argues that structure-agency duality does not happen automoatically. It requires a certain intervention to facilitate its praxis. It requires intervention that is more personal instead of general; and consider carefully the unique structure around woman (with ‘a’ not ‘e’) life in order to avoid the stereotype of women as single identity. However, despite the various structure surrounding women, there are similarity around women’s structure, namely: patriarchal norms and culture; violence against woman; and violation of woman’s right. Using reflective studies, the paper shows how financial inclusion program of Organization for Women in Self Employment (WISE) in Addis Ababa of Ethiopia serve as facilitator to the process; and enabling factor for woman’s agency . The WISE programs able to strengthen the capacity of individual woman who has to overcome the so many intersecting crises in her life that are physically and emotionally demanding. With joining the program, a vulnerable woman is able to develop her agency channelling to her mental health and well-being; as well as holding safety and care spaces. Stories from WISE members shows how economy, in this case financial aspect, could not be separated from the interest of woman, specifically whom who are vulnerable. At the same time, woman’s prosperity could only be achieved by her agency, rights and dignity in economics life.